2020
DOI: 10.1039/d0nj04663a
|View full text |Cite
|
Sign up to set email alerts
|

Roles of niobium in the dehydrogenation of propane to propylene over a Pt/Nb-modified Al2O3 catalyst

Abstract: The application of Pt-based catalyst in propane dehydrogenation (PDH) was restricted by low propylene selectivity, metal sintering and carbon deposition. It is reported that the performance of catalyst is strongly...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The bands at 1469 and 1573 cm –1 belonged to the ν s (COO – ) and ν as (COO – ) modes of carboxylate species, respectively, indicating that propane could react with the active oxygen species on the Pt/Nb 2 O 5 catalyst surface . Besides, the bands at 1652, 1620, and 1448 cm –1 were attributed to the CC group, the ν as (CH 2 CH–O – ) mode of enolate species, and allyl species, respectively, clearly implying that an acrylate pathway occurred on the Pt/Nb 2 O 5 catalyst in propane oxidation. , It was reported that Pt catalysts on niobium oxide possess excellent performance in the dehydrogenation of propane, which can render the initial reaction process involving an oxidative dehydrogenation of propane into propene, rather than an overoxidation into propionate and oxidative addition into isopropoxide species. , When the feed gas was switched into a C 3 H 8 and O 2 mixture, the bands related to enolate, CC groups, and allyl species disappeared quickly. In contrast, the peaks at 1544, 1452, and 1425 cm –1 belonged to monodentate carbonate (m-CO 3 2– ), carboxylate (RCOO – ), and bicarbonate (HCO 3 – ) species, respectively (Figure S20B).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The bands at 1469 and 1573 cm –1 belonged to the ν s (COO – ) and ν as (COO – ) modes of carboxylate species, respectively, indicating that propane could react with the active oxygen species on the Pt/Nb 2 O 5 catalyst surface . Besides, the bands at 1652, 1620, and 1448 cm –1 were attributed to the CC group, the ν as (CH 2 CH–O – ) mode of enolate species, and allyl species, respectively, clearly implying that an acrylate pathway occurred on the Pt/Nb 2 O 5 catalyst in propane oxidation. , It was reported that Pt catalysts on niobium oxide possess excellent performance in the dehydrogenation of propane, which can render the initial reaction process involving an oxidative dehydrogenation of propane into propene, rather than an overoxidation into propionate and oxidative addition into isopropoxide species. , When the feed gas was switched into a C 3 H 8 and O 2 mixture, the bands related to enolate, CC groups, and allyl species disappeared quickly. In contrast, the peaks at 1544, 1452, and 1425 cm –1 belonged to monodentate carbonate (m-CO 3 2– ), carboxylate (RCOO – ), and bicarbonate (HCO 3 – ) species, respectively (Figure S20B).…”
Section: Resultsmentioning
confidence: 96%
“…34 Besides, the bands at 1652, 1620, and 1448 cm −1 were attributed to the C�C group, the ν as (CH 2 �CH− O − ) mode of enolate species, and allyl species, respectively, clearly implying that an acrylate pathway occurred on the Pt/ Nb 2 O 5 catalyst in propane oxidation. 9,35 It was reported that Pt catalysts on niobium oxide possess excellent performance in the dehydrogenation of propane, which can render the initial reaction process involving an oxidative dehydrogenation of propane into propene, 21 rather than an overoxidation into propionate and oxidative addition into isopropoxide species. 9,11 When the feed gas was switched into a C 3 H 8 and O 2 mixture, the bands related to enolate, C�C groups, and allyl species disappeared quickly.…”
Section: Reaction Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Alumina is the most commonly used support for PDH due to its high surface area, thermal stability and mechanical strength. 75–78 The surface area, acid–base properties, and coordination structure of Al 2 O 3 have been demonstrated to have a significant influence on the catalytic performance of Pt-based catalysts. Accordingly, adjusting the morphology and surface properties of Al 2 O 3 can have an important effect on the resulting Pt-based catalysts.…”
Section: Support Effectmentioning
confidence: 99%
“…Alumina is the most commonly used support for PDH due to its high surface area, thermal stability and mechanical strength. [75][76][77][78] The surface area, acid-base properties, and coordination The interaction between Pt and the support has an important influence on the catalytic stability. It was found that unsaturated pentacoordinate Al 3+ centers present on the (100) facets of the g-Al 2 O 3 surface can anchor Pt.…”
Section: Alumina Supportmentioning
confidence: 99%